Pelatihan Kewirausahaan Berbasis Lingkungan bagi Pemberdayaan Ekonomi Jemaat GKPB Pniel Blimbingsari, Bali - Nyoman Fransiska; Gusti Ngurah Sukadana; Rudi Harisiswanto; Johan Johan; Cajenino Lorenco Ximenes (Journal Of Social Empowerment Publications, 2025)
Understanding the Economy of God's Kingdom as an alternative paradigm that integrates economic principles with biblical values. The critical context of the Pniel GKPB Blimbingsari congregation with a 30% decline in income, large but underutilized land potential, and limited knowledge of sustainable land management. Dependence on conventional production practices, limited market access, lack of business management knowledge, and agricultural practices that do not maintain environmental sustainability. The Environment-Based Entrepreneurship Service Program (KEKAL) integrates organic farming techniques (maggot fertilizer and fermented feed) with the spiritual and ethical values of the Kingdom of God according to Genesis 2:15. The method used is a mixture of qualitative and quantitative. The results of this service program showed a significant increase in the economic empowerment of the Kingdom of God (PEKA) by 50%, eco-theological behavior (PEKO) by 43.45%, with practical achievements in the form of 80% of participants producing their own organic fertilizer, spiritual transformation reaching 70%, and the conclusion that KEKAL is effective as a transformative entrepreneurship model that restores the relationship between humans, creation, and God.